Improving omega-3 fatty acid content in deep-fat fried sweet potato - Pongsing, W. (2018)
The fatty acid compositions of deep fat fried products depend on type of frying oil used. Improving the levels of essential fatty acids, principally omega-3 fatty acids (linolenic acid), can be effectively achieved by frying in blended oils instead of using a single oil. The aim of this research was to increase linolenic acid content in deep fat fried sweet potato by using blended oils (rice bran oil and canola oil). The fatty acid compositions, tocopherols and gamma-oryzanol contents of rice bran oil (RBO), canola oil (CNO) and blended oils (RBO:CNO-1=90:10v/v, RBO:CNO-2=80:20v/v) were determined using HPLC method. The physical properties of the oils were also determined. Thin sticks of sweet potato (8x8x80 mm) were blanched and dried to a moisture content of 67+2%. The dried-blanched sweet potatoes were deep fried in selected blended oil at 170°C for 3.5 min. The fatty acid compositions, tocopherols and gammaoryzanol contents of the fried product were determined. The results show that the chemical and physical properties of the frying oils depended significantly on the type oils and the blending proportions. The blended oils, RBO:CNO-1 and RBO:CNO-2, had higher linolenic acid content than the rice bran oil (p≤0.05). RBO:CNO-2 contained significantly higher linolenic acid and tocopherols contents, and possessed a smoke point higher than RBO:CNO-1. The sweet potato fried in RBO:CNO-2 had moisture, oil and total solid contents as 29.82%, 7.47% and 92.20%, respectively. It retained proper nutrition values (i.e., linolenic acid 1.33g/100 gextracted oil, linoleic acid 14.61g/100 gextracted oil, δ-tocopherol 2.30 mg/kgextracted oil, ϒ-tocopherol 64.94 mg/kgextracted oil, α-tocopherol 145.21 mg/kgextracted oil and gamma-oryzanol 871.78 mg/kgextracted oil). This study shows the effectiveness of using the blended oils (RBO:CNO-2; 80:20 v/v) to improve omega-3 fatty acid level and natural antioxidants in fried sweet potato, which is considered to be a healthier snack.